In Vitro Assessment of 177Lu-Labeled Trastuzumab-Targeted Mesoporous Carbon@Silica Nanostructure for the Treatment of HER2-Positive Breast Cancer - Tunçel, Ayça; Maschauer, Simone; Prante, Olaf; Yurt, Fatma (Pharmaceuticals, 2024)
This study assessed the effectiveness of a trastuzumab-targeted 177Lu-labeled mesoporous Carbon@Silica nanostructure (DOTA@TRA/MC@Si) for HER2-positive breast cancer treatment, focusing on its uptake, internalization, and efflux in breast cancer cells. The synthesized PEI-MC@Si nanocomposite was reacted with DOTA-NHS-ester, confirmed by the Arsenazo(III) assay. Following this, TRA was conjugated to the DOTA@PEI-MC@Si for targeting. DOTA@PEI-MC@Si and DOTA@TRA/MC@Si nanocomposites were labeled with 177Lu, and their efficacy was evaluated through in vitro radiolabeling experiments. According to the results, the DOTA@TRA/MC@Si nanocomposite was successfully labeled with 177Lu, yielding a radiochemical yield of 93.0 ± 2.4%. In vitro studies revealed a higher uptake of the [177Lu]Lu-DOTA@TRA/MC@Si nanocomposite in HER2-positive SK-BR-3 cells (44.0 ± 4.6% after 24 h) compared to MDA-MB-231 cells (21.0 ± 2.3%). The IC50 values for TRA-dependent uptake in the SK-BR-3 and BT-474 cells were 0.9 µM and 1.3 µM, respectively, indicating affinity toward HER-2 receptor-expressing cells. The lipophilic distribution coefficients of the radiolabeled nanocomposites were determined to be 1.7 ± 0.3 for [177Lu]Lu-DOTA@TRA/MC@Si and 1.5 ± 0.2 for [177Lu]Lu-DOTA@PEI-MC@Si, suggesting sufficient passive transport through the cell membrane and increased accumulation in target tissues. The [177Lu]Lu-DOTA@TRA/MC@Si nanocomposite showed an uptake into HER2-positive cell lines, marking a valuable step toward the development of a nanoparticle-based therapeutic agent for an improved treatment strategy for HER2-positive breast cancer.
CRIS-Team Scopus Importer:2024-07-12
Keywords: HER2+ breast cancer; mesoporous carbon and silica nanomaterials; radiolabeling